The subject and tasks of the science of youth psychology - Botirova M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article talks about the subject, methods, departments of youth and pedagogical psychology, education, upbringing and teacher psychology. The chapter on educational psychology describes the psychological essence of educational activities, psychological components of knowledge acquisition, non-traditional methods of education, development of independent thinking, management of the educational process. In the chapter of educational psychology, psychological mechanisms that increase the effectiveness of education, in the chapter of teacher psychology, pedagogic skills, requirements for the teacher's personality are discussed.